2015
DOI: 10.1149/2.0171511jes
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Highly Ordered Monolayers of Nanoparticles Fabricated Using Electrophoretic Deposition: Cobalt Ferrite Nanoparticles versus Iron Oxide Nanoparticles

Abstract: Ordered assemblies of nanoparticles remain challenging to fabricate, yet could open the door to many potential applications of nanomaterials. Here, we demonstrate that locally ordered arrays of nanoparticles, using electrophoretic deposition, can be extended to produce long-range order among the constituents. Voronoi tessellations along with multiple statistical analyses show dramatic increases in order compared with previously reported assemblies formed through electric field-assisted assembly. Based on subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…3C). These particle physicochemical characteristics are consistent with CF nanoparticles produced by other methods, suggesting that the solvothermal process used did not cause morphological changes to the nanoparticles [4850]. To further characterize the synthesized magnetite particles, HR-TEM and SAED diffraction analysis was performed.…”
Section: Resultssupporting
confidence: 78%
“…3C). These particle physicochemical characteristics are consistent with CF nanoparticles produced by other methods, suggesting that the solvothermal process used did not cause morphological changes to the nanoparticles [4850]. To further characterize the synthesized magnetite particles, HR-TEM and SAED diffraction analysis was performed.…”
Section: Resultssupporting
confidence: 78%
“…31 Replacing Fe ions in interstitial sites with different metal ions such as Mn, Zn, Ga, Ni, Co or Cu will improve Fe 3 O 4 unique physical z E-mail: hanaa_eldesoky@Science.tanta.edu.eg; mhmubark@Science.tanta.edu.eg properties which originate from electrons hopping between Fe 2+ and Fe 3+ ions. [32][33][34][35][36] Xu et al, 25 reported that doping Mn Fe 3 O 4 NPs could provide a synergistic effect with Fe species for higher electrochemical reactivity.…”
mentioning
confidence: 99%
“…1-2 μm. [49][50][51][52][53][54] Recently, through several iterations and designs of experiments, new EPD parameters for successful iron oxide nanoparticle thick film fabrication (approximately 10 μm) were achieved. 29 Parameters such as particle concentration, molarity of the EPD bath solution, electrode-electrode distance, and deposition time were varied in order to obtain films that were sufficiently thick and crack free.…”
Section: Electrophoretic Depositionmentioning
confidence: 99%
“…For 0‐3 magnetic nanocomposites for power component applications, there is a need for a robust, novel modification to the method in order to deposit magnetic nanoparticles via EPD into micron‐thick films. Previously, the EPD of magnetic oxide nanoparticles was not utilized to fabricate magnetic nanocomposites, due to a focus on monolayer film formation, and the fact that these were often not able to achieve film thicknesses above 1–2 μm 49–54 . Recently, through several iterations and designs of experiments, new EPD parameters for successful iron oxide nanoparticle thick film fabrication (approximately 10 μm) were achieved 29 …”
Section: Magnetic Nanoparticle Film Fabricationmentioning
confidence: 99%